UiT goes open – innledningen til et festlig skrift - Aspaas, Per Pippin; Ekanger, Aysa; Raade, Johanne (Ravnetrykk, 2020)
In the spring semester of 2020, Stein Høydalsvik turns 67. At the same time, he retires from his job, after having spent 23 full years of his career in the service of a university and its library. With the help of Stein, UiT The Arctic University of Norway has become a pioneer in the field of Open Science. Several aspects of Open Science that have gained currency in Norwegian academia were first piloted at UiT with Stein as pathfinder. To name only some examples, open journal publishing, a national service for the curation of research data, services for open sharing of master theses and doctoral dissertations have been implemented and improved in recent years. An internationally acclaimed conference on scholarly publishing has been established, along with a publication fund for Open Access fees, massive archiving of peer-reviewed article manuscripts. A global, free-to-use portal for openly available research datasets and publications on the Arctic and Antarctic is in the making. There are few persons that manage to accomplish as much as Stein. He has not done it all by himself, of course. Nevertheless, behind a wide range of activities at UiT and at the University Library in particular, Stein has been either the initiator or the inspirer. It is his lifework as employee of UiT that we now celebrate.